Anniversary of the International Labour Organization: the centenary and prospects - D. K. Bekyashev; V. G. Mikrina (Московский журнал международного права, 2019)
INTORDUCTION. The International Labour Organization (ILO) is a specialized Agency of the United Nations, established in 1919 on the basis of the Treaty of Versailles. The competence of this Organization, among other things, includes standard-setting activities for the development of labor standards at the international level. In 2019, the ILO celebrates 100 years since its creation. This article analyzes the current activities of the Organization to improve the existing international legal norms, as well as the prospects for the development of rulemaking planned for the upcoming years. In particular, special attention is paid to a set of measures aimed at solving urgent problems affecting profound changes in the sphere of labor at the international level. Among the tasks that the ILO plans to give priority to in the nearest future are the finalization and unification of the international legal norms adopted by the Organization, as well as the development of new conventions aimed at improving the international legal regulation of labor.MATERIALS AND METHODS. Present study is based on the analysis of the current legal framework of the Organization, aimed at improving the international legal norms on labor. In addition, the works of Russian and foreign scientists on the chosen subject were used. General scientific and special methods of cognition, including comparative legal and formal legal, are used as a method of research.RESEARCH RESULTS. The authors' analysis of the ILO's work on improving international legal norms on labour, showed that, at the present time clearly indicated the intention of the Organization to organize homogeneous in its content of norms regulating the issues of occupational safety, hygiene and security in the workplace. At the same time, the ILO has set itself the task of updating existing norms and abolishing those that are largely outdated and ineffective. In addition, the Organization's activities in the upcoming years will also focus on the audit of outdated standards and other regulatory issues. Also, taking into account statistical indicators, according to the authors, there is an urgent need for the adoption of a new ILO Convention aimed at combating violence and harassment in the workplace.DISCUSSION AND CONCLUSIONS. In accordance with the objectives and changes in the international legal regulation of labour relations, the ILO Global Commission on the Future of Work has identified the most acute problems and challenges, the overcoming of which will open up new prospects for future generations in the field of labour, namely: the revision of existing international labour standards, the abolition of obsolete, the codification of homogeneous rules governing occupational safety, security and hygiene. Great importance is also given to the improvement and progressive development of international labour law. In this regard, the authors believe that there is a need for the ILO to develop and adopt a Convention to combat violence and harassment in the workplace. The new international legal instrument should provide mechanisms for protection against violence and harassment, which could give greater weight to the problem by covering all workers and all forms of violence and harassment, and by addressing the issue in a comprehensive and integrated manner. The drafting and adoption of an international Treaty on the subject would be extremely important, since violence and harassment were unacceptable and were the opposite of the concept of "decent work" adopted by the ILO in 1999.